1976
DOI: 10.1063/1.432192
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra and normal coordinate analysis of bromochlorofluoromethane

Abstract: Raman spectra (50–4000 cm−1) of the gaseous, liquid, and solid phases along with gas-phase infrared spectra (200–4000 cm−1) of four isotopic species of bromochlorofluoromethane HCBr35ClF, HCBr37ClF, DCBr35ClF, and DCBr37ClF have been observed. Data from all three phases were needed to make a detailed vibrational assignment since Fermi resonance enhancement of several overtone and combination modes results in a rather complex spectrum. Twenty-four distinct gas-phase frequencies were used to calculate a generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Our somewhat historical introduction on CHBrClF would be incomplete without noting that this molecule was used by van't Hoff to illustrate theoretical concepts of chirality. 69 Low-resolution vibrational spectra (including circular dichroism) had been obtained in the past [70][71][72][73][74] and moderately high-resolution photoelectron spectra have been reported recently. 75 Figure 1 shows the pair of enantiomers for CHBrClF and the corresponding energy level scheme to set the stage for the following calculations.…”
Section: Chbrclf: Chemistry High Resolution Spectroscopy and Paritymentioning
confidence: 99%
“…Our somewhat historical introduction on CHBrClF would be incomplete without noting that this molecule was used by van't Hoff to illustrate theoretical concepts of chirality. 69 Low-resolution vibrational spectra (including circular dichroism) had been obtained in the past [70][71][72][73][74] and moderately high-resolution photoelectron spectra have been reported recently. 75 Figure 1 shows the pair of enantiomers for CHBrClF and the corresponding energy level scheme to set the stage for the following calculations.…”
Section: Chbrclf: Chemistry High Resolution Spectroscopy and Paritymentioning
confidence: 99%
“…[51] In addition, CDBrClF has been investigated together with CHBrClF in the fundamental region at lower resolution. [52][53][54] Studies of its vibrational circular dichroism [55] and its Raman optical activity [56] have been reported. This molecule has also been investigated to study the effects of coupled anharmonic vibrations on molecular parity violation.…”
mentioning
confidence: 99%
“…The vibrational spectrum of CDBrClF has been analyzed from the FIR to the NIR region (Beil et al 2000). In addition, CDBrClF has been investigated together with CHBrClF in the fundamental region at lower resolution (Diem and Burow 1976, 1977, Diem et al 1978. Studies of its vibrational circular dichroism (Marcott et al 1977) and its Raman optical activity (Prasad and Burow 1979) have been reported.…”
Section: Overview Of the Articlementioning
confidence: 99%